2019
DOI: 10.1097/mpa.0000000000001310
|View full text |Cite
|
Sign up to set email alerts
|

Apigenin Decreases Acinar Cell Damage in Pancreatitis

Abstract: Objective: Chronic pancreatitis is the consequence of multiple episodes of recurrent acute pancreatitis (RAP). We hypothesized that apigenin can minimize the sequelae of RAP by limiting acinar cells' pro-inflammatory signaling pathways. Methods: AR42J acinar cells were treated in vitro with transforming growth factor beta (TGF-β), apigenin, and other inhibitors. Dual luciferase reporter assay measured parathyroid hormone related protein (PTHrP) promoter activity. MAPK/ERK pathway activity was assessed by immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Thus, pancreatic ductal cells play critical roles in injury in AP. However, previous studies on AP have focused on pancreatic acinar cells (13)(14)(15), while studies on pancreatic ductal cells are limited (7).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, pancreatic ductal cells play critical roles in injury in AP. However, previous studies on AP have focused on pancreatic acinar cells (13)(14)(15), while studies on pancreatic ductal cells are limited (7).…”
Section: Introductionmentioning
confidence: 99%
“…53 The ability to selectively target multiple different cell types in CP can open a new avenue for therapeutic strategies that address the crosstalk between ECM components and aPSCs, which initiates multiple cascades of events in fibrogenesis and inflammation in CP. 12 , 54 Indeed, we demonstrated that targeting apigenin to the ECM demonstrated enhanced pharmacodynamic effects beyond that of targeting macrophages alone with NP liposomes, underscoring the importance of targeting. Apigenin is a small molecule drug that has been shown to have antifibrotic, anti-inflammatory, and proapoptotic effects in cancer and chronic inflammatory diseases in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 73%
“…Apigenin is a small molecule natural compound, that has been demonstrated preclinically to have antifibrotic and anti-inflammatory properties in CP. 11 , 12 Apigenin, however, suffers from low aqueous solubility, metabolic instability, and off-target effects and there are no approved clinical applications of apigenin available. 21 , 36 , 37 Therefore, we used apigenin as a proof of concept and directly loaded it into the MDLSLKP-conjugated liposomes (ECM liposome).…”
Section: Resultsmentioning
confidence: 99%
“…Flavonoids from most subgroups have been evaluated for potential protective effects in AP. For example, genistein (isoflavone) [ 31 ], quercetin (flavonol) [ 32 ], naringenin (flavanone) [ 33 ], apigenin (flavone) [ 34 ], dihydromyricetin (flavanonol) [ 35 ], luteolin (flavone) [ 36 ], and fisetin (flavonol) [ 37 ] either suppressed inflammation, prevented acinar cell damage, or both [ 38 , 39 ]. Tricetin (TCT) ( Supplementary Figure S1B ) is a flavone compound with likely or proven bioactivity in models of neurotoxicity, Parkinson’s disease [ 40 ], diabetes [ 41 , 42 ], and bacterial infections [ 43 ].…”
Section: Introductionmentioning
confidence: 99%